The Influence Of Job Satisfaction, Perceived Organizational Support, And Work-Life Balance On Turnover Intention Through The Mediation Of Organizational Commitment - Ayunda Putri; Harits Hijrah Wicaksana (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The rising phenomenon of employee turnover has become a serious concern for organizations, as it negatively affects productivity, employee morale, and the continuity of business operations. This study aims to analyze the effect of job satisfaction, perceived organizational support, and work-life balance on turnover intention, with organizational commitment as a mediating variable. A quantitative approach was employed using stratified random sampling, involving 210 permanent employees at PT Jembo Cable Company Tbk. Data were analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The results indicate that job satisfaction and work-life balance have a positive influence on organizational commitment, while perceived organizational support does not show a significant effect. Organizational commitment was proven to reduce turnover intention and mediate the relationship between job satisfaction and work-life balance with turnover intention. However, the relationship between perceived organizational support and turnover intention is not mediated by organizational commitment, and its direct effect on turnover intention does not align with the hypothesized direction. These findings highlight that enhancing job satisfaction and work-life balance is essential for strengthening employee commitment to the organization, thereby reducing turnover intention more effectively and sustainably.